Improvement of Agrarian Relations as a Prerogative of the State - Maleichenko, Vyacheslav N.; Artyomova, Elena I.; Zelinskaya, Maria V. (International Review of Management and Marketing, 2016)
The paper proves that agrarian relations do not fit for the system of modern market mechanisms because their commercialization adverse to the capital interests and social and economic relations humanization. There are objective circumstances causing a prerogative of the state concerning the development and improvement of agrarian relations. First of all, the main criterion of authority statehood is achievements in ensuring food sovereignty and total adequate provision with food supplies for healthy lifestyle. Thus, exactly the state, not the market, has to stimulate the most rational forms of production and land use. Agriculture is the sphere where the interests of entrepreneurship have to be focused not on the market, but on the general state interests. The laisser-faire in this sphere has to be expressed in conscious, effective work on the state interest. Keywords: management of agriculture, food security, agrarian policy JEL Classifications: J5; Q18